Pseudoangiomatous stromal hyperplasia of the breast presenting as gigantomastia: case report - Farias, Juliana Pontes; Guedes Neto, Humberto Espínola; Suassuna, Ariano Brilhante Pegado; Queiroga, Rafael Chaves Claudino de; Nunes, Arthur Antonino da Silva; Quirino, Adriano de Lima; Medeiros, Thaíse Lopes (Mastology, 2020)
Pseudoangiomatous stromal hyperplasia (PASH) of the breast is a benign condition generally seen as an incidental finding of biopsies for other causes. In some rare cases, it can evolve with expressive growth of breast tissue, leading to large breasts. The present study presents a case report of a patient who started with breast hypertrophy during lactation, evolving with gigantomastia, and arrived at the office 3 years after gestation with breasts of 6.2 and 4.3 kg and growth of accessory breast and axillary lymph nodes. The patient was emaciated, with bodily pain and psychological distress. Computed tomography was performed with the finding of diffuse retroglandular nodules and axillary and mediastinal lymph node enlargement, without being able to rule out the lymphoproliferative process. Then, core biopsies were made in several places on the breast whose pathological examination revealed PASH samples. Bilateral mastectomy was performed as a surgical treatment, with resection of the left accessory breast and left axillary lymph node, and breast reconstruction, with placement of silicone prostheses and graft of the areola-papillary complex, together with a plastic surgeon. She evolved in the postoperative period with good healing of the surgical wound, weight gain, necrosis of the areola-papillary complex and with severe psychiatric disorder, which was treated appropriately by psychiatrists, with remission of symptoms. This case report presents a rare evolution of PASH with gigantomastia, bringing intense physical and psychological distress to the patient, whose treatment chosen was total surgical resection of the breast tissue and aesthetic reconstruction.